Exploring men’s perceptions of Intimate Partner Violence in heterosexual relationships: a case study of Munsieville - Ntombini, Ayanda Veronica (My University, 2017)
In South Africa, violence has become normal and, to some degree, accepted rather than challenged. As a result, South Africa is known as a country that is informed by the ‘culture of violence’. This study explored men’s perceptions of Intimate Partner Violence (IPV) in heterosexual relationships in Munsieville, Krugersdorp. Drawing on the imbalance theory, the researcher explored men’s perceived understanding of Intimate Partner Violence as both perpetrators and protectors. The study was carried out using qualitative research approach that was exploratory in nature. A non-probability, purposive sampling procedure was applied when identifying and recruiting participants for the study. A sample consisting of 12 men, who reside in Munsieville, was collected. In-depth, face to face and semi-structured interviews were conducted and Thematic Analysis was used to analyse the data. The findings indicated that, the men’s perceived understanding of intimate partner violence was largely informed by their perceived understanding of what an intimate partner relationship is. Ideas of love and the level of reciprocity seemed to precipitate violence, especially in instances where a woman refused to reciprocate. The men reported direct and indirect experiences to Intimate partner violence. This indicated that Intimate Partner Violence was a problem in Munsieville, although there was no surety on the extent of the problem. Ideas of femininity and masculinity, patriarchy emerged as some of the factors that perpetuated Intimate Partner Violence in the community. Moreover, Income imbalance, substance abuse and childhood exposure were also reported as contributing to Intimate partner violence. The study also revealed that men were largely the perpetrators and women were the victims. Recommendations were provided for the development of prevention strategies to reduce the occurrence of IPV and as well as future studies. Key words: Intimate Partner Violence, Domestic violence, South Africa, Gender, heterosexual relationships.